ANALISIS PENGARUH RASIO AKTIVITAS TERHADAP PROFITABILITAS PADA PT. BARATA INDONESIA (PERSERO) UUM MEDAN - Fatima Anum ., Muhammad Basri (Jurnal Riset AKuntansi dan Bisnis, 2014)
This research was done at PT. Barata Indonesia (Persero) UUM Medan. Thisresearch aims to prove emprically the influence of the variables cash turnover,receivable turnover, days of receivanle, fixed asset turnover and total assets turnoverto the profitability of the company. Technical data analysis using non parametricstatistics with hypothesis testing using Spearman and Kendall correlation. Theresults of this research show that the variables cash turnover, receivable turnover,days of receivable, fixed asset turnover and total assets turnover effect was notsignificant the profitability at PT. Barata Indonesia (Persero) UUM Medan 2005-2013. Other factors which influence significantly to profitability (gross profitmargin) which are the other variables outside of the variables are used in thisresearch are the amount and the sale price per unit, cost of goods sold, liquidity andlabor productivity.